Fat Grafting and the Palpable Breast Mass in Implant-Based Breast Reconstruction: Incidence and Implications. Issue 2 (August 2019) - Knackstedt, Rebecca W.; Gatherwright, James; Ataya, Dana; Duraes, Eliana F. R.; Schwarz, Graham S.
Abstract : Background: Fat grafting is a powerful and increasingly used technique in breast reconstruction. However, fat necrosis can lead to palpable postoperative changes that can induce anxiety and lead to unplanned diagnostic studies. The authors' aim in this study was to evaluate the incidence, type, and timing of these unanticipated studies; the specialty of the ordering provider; and the factors that trigger the ordering process. Methods: A retrospective chart review was conducted for patients from 2006 to 2015 who underwent fat grafting as part of implant-based breast cancer reconstruction and had at least 1-year follow-up after fat grafting. Results: From 2006 to 2015, 166 patients underwent fat grafting as part of implant-based breast reconstruction. Forty-four women (26.5 percent) underwent at least one imaging procedure. Thirteen women (7.8 percent) underwent 17 biopsies. For a palpable mass, the initial imaging test most commonly ordered was ultrasound, followed by mammography/ultrasound. The percentage of patients with a diagnosis of fat necrosis on mammography, ultrasound, and biopsy was 4.2, 12.7, and 5.4 percent, respectively. Seven patients (4.2 percent) had distant metastases. Tissue diagnosis of local recurrence was never identified. Mean follow-up was 2.4 years. Conclusions: Fat-grafting sequelae may lead to early unplanned invasive and noninvasive procedures initiated by a variety of providers. In this study, fat grafting had no impact on local recurrence rate. As use of fat grafting grows, communication among breast cancer care providers and enhanced patient and caregiver education will be increasingly important in optimizing the multidisciplinary evaluation and monitoring of palpable breast lesions. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.